2019
DOI: 10.1186/s13054-019-2478-6
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and mortality of septic shock in Europe and North America: a systematic review and meta-analysis

Abstract: Background Septic shock is the most severe form of sepsis, in which profound underlying abnormalities in circulatory and cellular/metabolic parameters lead to substantially increased mortality. A clear understanding and up-to-date assessment of the burden and epidemiology of septic shock are needed to help guide resource allocation and thus ultimately improve patient care. The aim of this systematic review and meta-analysis was therefore to provide a recent evaluation of the frequency of septic sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
210
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(252 citation statements)
references
References 106 publications
(81 reference statements)
18
210
1
1
Order By: Relevance
“…Although the absolute mortality has decreased from 35.0% to 18.4% in patients with severe sepsis in the areas of Australia and New Zealand during the last decades [7], one recent systematic review revealed the ICU mortality of sepsis in Europe and North America remains 37.3%, where the morbidity was estimated at 10.4% [8]. It is similar to these studies that the 28-day mortality was 42.9% in our study.…”
Section: Discussionsupporting
confidence: 83%
“…Although the absolute mortality has decreased from 35.0% to 18.4% in patients with severe sepsis in the areas of Australia and New Zealand during the last decades [7], one recent systematic review revealed the ICU mortality of sepsis in Europe and North America remains 37.3%, where the morbidity was estimated at 10.4% [8]. It is similar to these studies that the 28-day mortality was 42.9% in our study.…”
Section: Discussionsupporting
confidence: 83%
“…Sepsis and the more severe form, septic shock, are devastating conditions with high mortality and morbidity caused by a systemic infection leading to organ dysfunction (1,2). A recent extensive systemic review of observational studies from North America and Europe showed that 10% of patients admitted to intensive care units (ICU) were diagnosed with septic shock, with an ICU mortality of 38% (3). Gramnegative bacteria are the most common group of sepsis-causing organism (62%), but the incidence of gram-positive bacteria has increased in frequency over time (4).…”
Section: Introductionmentioning
confidence: 99%
“…Background 3 Sepsis and the more severe form, septic shock, are devastating conditions with high mortality and morbidity caused by a systemic infection leading to organ dysfunction (1,2). A recent extensive systemic review of observational studies from North America and Europe showed that 10% of patients admitted to intensive care units (ICU) were diagnosed with septic shock, with an ICU mortality of 38% (3). Gram-negative bacteria are the most common group of sepsis-causing organism (62%), but the incidence of gram-positive bacteria has increased in frequency over time (4).…”
Section: Introductionmentioning
confidence: 99%